The Moon - Simon, Seymour (New York : Four Winds Press, 1984)
A basic introduction to Earth's closest neighbor, its composition, and man's missions to it. Illustrated with photographs of the moon taken in space.
Keywords: Moon -- Juvenile literature; Moon -- Photographs from space